2013
DOI: 10.1089/aid.2012.0281
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization and Transmitted Drug Resistance of the HIV Type 1 Epidemic in Men Who Have Sex with Men in Beijing, China

Abstract: A rapid increase in the number of HIV cases in the men who have sex with men (MSM) population has been observed in China; however, little information is available on the genetic characterization of HIV prevalent in this population. In this study, 95 HIV-1-seropositive drug-naive patients from the Beijing MSM population were enrolled. The genetic characterization and transmission of drug resistance of HIV-1 were examined based on fulllength gag, pol, and partial env gene sequences. Three subtypes, including CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…On the contrary, TDR related to NNRTI and NRTI were much less frequent. Previous studies had similar findings (12,13,19). Lin Li et al found four cases carrying a TDR mutation in 76 strains among Beijing MSM patients.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…On the contrary, TDR related to NNRTI and NRTI were much less frequent. Previous studies had similar findings (12,13,19). Lin Li et al found four cases carrying a TDR mutation in 76 strains among Beijing MSM patients.…”
Section: Discussionsupporting
confidence: 53%
“…Lin Li et al found four cases carrying a TDR mutation in 76 strains among Beijing MSM patients. All four cases were M46I mutations, and all of them belonged to CRF01_AE strains (13).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[8][9][10][11][12][13] This CRF was first identified in the intravenous drug use (IDU) population in Xinjiang province in 1997, 8,9 but recent studies have shown that CRF07_BC has been introduced into the men who have sex with men (MSM) population, suggesting that it has spread to different regions of China and across different high-risk groups. 14,15 Several studies were carried out in China to analyze the transmission and spread of the CRF07_BC strain, resulting in two hypotheses to address the temporal and spatial dynamic of the spread of CRF07_BC in the country. One hypothesis suggests that CRF07_BC originated in Yunnan and spread to Sichuan, Gansu, and finally to Xinjiang province along the drug trade route.…”
mentioning
confidence: 99%
“…A recent meta-analysis also reported a pooled TDR prevalence of 2.9% from seven low- and middle-income countries in South and Southeast Asia [13]. Several studies of MSM cohorts in China have reported similar TDR prevalences of 4.6 to 5.3% [16,32]. …”
Section: Discussionmentioning
confidence: 99%